MAS NMR and EPR study of structural changes in talc and montmorillonite induced by grinding. (2nd January 2018) - Borges, Roger; Dutra, Lívia Macedo; Barison, Andersson; Wypych, Fernando
Abstract: The milling process in the solid-state 2:1 clay minerals, montmorillonite and talc, which have different cation exchange capacities, is reported here. Several instrumental techniques were used to monitor systematically the products formed. The dehydroxylation/amorphization of the montmorillonite and talc structures occurs within 3 and 6 h of milling, respectively. Electron paramagnetic resonance spectra indicated that structural Mn2 + was oxidized more quickly in the montmorillonite structure than in talc, while the paramagnetic defects increased during milling. Nuclear magnetic resonance was also used to monitor the environmental changes for Si and Al during milling.